Survival and Complications of Single Dental Implants in the Edentulous Mandible Following Immediate or Delayed Loading: A Randomized Controlled Clinical Trial - Matthias Kern; Wael Att; Elfriede Fritzer; Stefanie Kappel; Ralph G. Luthardt; Torsten Mündt; Daniel R. Reißmann; Martin Rädel; Meike Stiesch; Stefan Wolfart; Nicole Passia (2017)
It was the aim of this 24-mo randomized controlled clinical trial to investigate whether the survival of a single median implant placed in the edentulous mandible to retain a complete denture is not compromised by immediate loading. Secondary outcomes were differences in prosthetic complications between the loading principles. Each of the 158 patients who received an implant was randomly assigned to the immediate loading group ( n = 81) or the delayed loading group ( n = 77). Recall visits were performed 1 mo after implant placement (for only the delayed loading group) and 1, 4, 12, and 24 mo after implant loading. Nine implants failed in the immediate loading group, all within the first 3 mo of implant loading, and 1 implant failed in the delayed loading group prior to loading. Noninferiority of implant survival of the immediate loading group, as compared with the delayed loading group, could not be shown ( P = 0.81). Consistent with this result, a secondary analysis with Fisher exact test revealed that the observed difference in implant survival between the treatment groups was indeed statistically significant ( P = 0.019). The most frequent prosthetic complications and maintenance interventions in the mandible were retention adjustments, denture fractures, pressure sores, and matrix exchanges. There was only 1 statistically significant difference between the groups regarding the parameter “fracture of the denture base in the ball attachment area” ( P = 0.007). The results indicate that immediate loading of a single implant in the edentulous mandible reveals inferior survival than that of delayed loading and therefore should be considered only in exceptional cases (German Clinical Trials Register: DRKS00003730).